Proses Perancangan Buku Vector Ragam Hias Wayang Gagrak Surakarta - Lintang Widyokusumo (Humaniora, 2014)
In the early stages of gagrak puppet ornaments book designing of Surakarta, digitally process documentation is done. Source images with poor conditions are transferred through the tracing process that requires precision to produce documentation of images with sharp vector format. Diversity of gagrak puppet ornaments and accessories are tried to be compiled in a book with a grid system that is expected to be a reference book of attractive gagrak puppets ornaments in a contemporary appearance. Article is based on a literature review by selecting multiple sources of both printed and electronic and doing some sketches of various shapes observation, shapes and textures. A collection of ornaments in the notion that is processed from the 'old values' that have been there that will be applied to 'new value' a masterpiece of design that can be universally accepted and globally